The case of the missing remittances in the FIES: Could it be causing us to mismeasure welfare changes? - Geoffrey Ducanes (University of the Philippines, School of Economics (UPSE), 2010)
This paper highlights the increasing underreporting of remittances by the FIES compared to BSP and World Bank figures, advances possible reasons why such underreporting is occurring, and examines its implications for welfare measurement in the country at points in time and across time. Using simulation exercises, the paper finds that indeed the 'missing remittances' in the FIES could be causing the mismeasurement of poverty and inequality since 1997, possibly clouding the direction of welfare change.
Keywords: 330; Rücküberweisung (Migranten); Messung; Entwicklungsindikator; Sozialer Wandel; Philippinen